Gender Differences in the Psychopharmacological Treatment of Forensic In-Patients With Schizophrenia - Mayer, Juliane; Vasic, Nenad; Wolf, Viviane; Steiner, Ivonne; Klein, Verena; Fritz, Michael; Rothe, Philipp; Streb, Judith; Dudeck, Manuela (Frontiers in Psychiatry, 2022)
Background: In forensic psychiatry, psychopharmacological treatment plays a crucial role for patients with schizophrenia in improving their medical as well as legal prognosis. However, an increase in the number of females entering forensic treatment has yet to yield empirical research on the outcome of psychopharmacological treatment of female patients with schizophrenia in terms of efficacy and tolerability. Aims: The aim of the present study is to elucidate pharmacological treatment strategies of women with schizophrenia in forensic psychiatry in comparison with men. Methods: This study compares psychopharmacological treatment strategies, psychopathological features, and neurologic and metabolic side effects of treatment between 29 female and 29 male in-patients with schizophrenia in three forensic facilities in Bavaria, Germany. Results: Results show significant differences between genders. Poorer psychopathological and neurological features were found in the female sample, while men registered worse metabolic parameters. In terms of psychopharmacological treatment strategies, female in-patients were more often prescribed second-generation depot antipsychotics. Surprisingly, the potency of the dosages did not differ between genders. The results suggest that female forensic patients with schizophrenia have more severe and refractory diseases than their male counterparts. Conclusions: Recommendations for gender-specific treatment strategies are derived.